2023
DOI: 10.3390/su15032490
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Local Precise Reinforcement Method for Dynamic Stability of Rock Slope under Earthquakes Using Continuum–Discontinuum Element Method

Abstract: The slope reinforcement scheme has an important influence on the prevention and control of landslides. A reasonable reinforcement scheme can improve the reliability, economy and efficiency of landslide resistance. It is urgent to establish a local precise reinforcement method for landslides on the basis of clear process and the instability modes of landslides. Taking a high-steep anti-dip rock slope as an example, six numerical models are established by using the continuum–discontinuum element method (CDEM) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In order to reconcile the complex earthquake time history with the unduly simplistic pseudo-static approach, Steedman and Zeng (1990) developed and implemented the pseudo-dynamic approach for seismic slope stability analysis (Eskandarinejad and Shafiee 2011, Qin and Chian 2018, Zhou and Qin 2020. Song et al (2023) examined a localized, precise reinforcement technique for enhancing the dynamic stability of rock slopes during earthquakes through the application of the Continuum-Discontinuum Element Method. The findings underscore the importance of determining the dynamic amplification effect and seismic damage characteristics of slopes as a crucial prerequisite for implementing the local precise reinforcement method.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reconcile the complex earthquake time history with the unduly simplistic pseudo-static approach, Steedman and Zeng (1990) developed and implemented the pseudo-dynamic approach for seismic slope stability analysis (Eskandarinejad and Shafiee 2011, Qin and Chian 2018, Zhou and Qin 2020. Song et al (2023) examined a localized, precise reinforcement technique for enhancing the dynamic stability of rock slopes during earthquakes through the application of the Continuum-Discontinuum Element Method. The findings underscore the importance of determining the dynamic amplification effect and seismic damage characteristics of slopes as a crucial prerequisite for implementing the local precise reinforcement method.…”
Section: Introductionmentioning
confidence: 99%
“…Although the numerical simulation method is a repeatable and economical analysis method, the current research on anti-dip slope simulation is mainly based on finite element, finite difference, and traditional discrete element methods [31,[38][39][40]. Some scholars have also used new numerical methods, such as DDA, CDEM, and FDEM, which can effectively describe the fracture of rock or soil to conduct relevant research [41][42][43][44][45]. Liu et al [44] demonstrated the effectiveness of the FDEM method throughout the entire process simulation of anti-dip slope instability.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [44] demonstrated the effectiveness of the FDEM method throughout the entire process simulation of anti-dip slope instability. Song et al [45] adopted the CDEM method to conduct seismic damage and dynamic analysis on a high, steep, anti-dip rock slope. However, the application of the new methods above in analyzing the instability process and mechanism of the anti-dip slope is still relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [21] investigated the dynamic effects and failure mechanism of anti-dip bedding rock slopes under seismic loading using three-dimensional DEM, and the amplification effect, changes in the Fourier spectrum, failure mechanism, and permanent displacement of the slope caused by the applied seismic action were analyzed. In addition to the traditional FEM and DEM mentioned above, some novel numerical simulation methods (e.g., DDA, CDEM, and FDEM) have also been applied to analyze the stability of different rock slopes [3,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%